1994
DOI: 10.1002/bjs.1800811016
|View full text |Cite
|
Sign up to set email alerts
|

Saphenous vein reflux without incompetence at the saphenofemoral junction

Abstract: Duplex ultrasonography was used to assess patients with primary varicose veins to determine whether varicosities of the long saphenous vein (LSV) occurred without saphenofemoral junction (SFJ) incompetence. Some 167 consecutive patients with the clinical diagnosis of primary varicose veins were investigated. Of 190 limbs with LSV reflux 63 had no SFJ incompetence, of which only five had incompetent perforators; these were midthigh perforators in two limbs and medial calf perforators in three. LSV reflux often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
46
1
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(60 citation statements)
references
References 19 publications
9
46
1
4
Order By: Relevance
“…[31][32][33] We found a significant difference in the number of both tributaries and valves. On the other hand, data from a French study showed no difference between the left and right side.…”
Section: The Idealized Saphenofemoral Junctionmentioning
confidence: 65%
“…[31][32][33] We found a significant difference in the number of both tributaries and valves. On the other hand, data from a French study showed no difference between the left and right side.…”
Section: The Idealized Saphenofemoral Junctionmentioning
confidence: 65%
“…2 This description was also challenged regularly by studies describing the presence of varices that were not necessarily accompanied by SV incompetence. [3][4][5][6][7][8][9][10][11] Nevertheless, the Trendelenburg theory remained very widely dominant, having as a consequence the dogma of the elimination of the SV and of all of the points of reflux, starting with the deep veins (including, in particular, in the region of the saphenous confluence), by high ligation at the deep vein level, in accordance with the principles described by Mayo 12 and Babcock 13 at the start of the 20th century.…”
mentioning
confidence: 98%
“…Furthermore, most of the patients presented symptoms, and we observed SFC reflux in 80.5% of the cases, whereas the rate is usually 50% in the literature if there is saphenous reflux. [1][2][3][4][5][6] In fact, the surgery we performed was relatively extensive: long stripping in nearly half the cases, with an average of 40 associated phlebectomies and a mean operation duration of 80 minutes. Yet, in our study, we observed no reflux in the preserved SFC in 98.2% of cases with a mean follow-up period of 24.4 months.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature The frequency of sub-ostial or more distal trunk reflux was evaluated at around 50%. [1][2][3][4][5][6] Endovenous treatments for GSV reflux have called into question the principle of ligation of all tributaries at the sapheno-femoral confluence, so called "crossectomy", leaving the sapheno-femoral confluence (SFC) in place upstream of the preostial valve. 7,8 Results of endovenous techniques show that SFC reflux frequency in the medium term does not exceed 15%, with anterograde drainage of the SFC collaterals towards the femoral vein in 85% to 100% of cases.…”
mentioning
confidence: 99%